Teknik Array pada Antena Mikrostrip Patch Rectangular dengan Slot Persegi Panjang Dan Slot T pada Groundplane untuk Meningkatkan Gain Antena - lathifa Lathifatus Sholihah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The development of increasingly sophisticated and digital information technology. Fast and real-time communication by utilizing technology to exchange data using a high internet connection. WiFi (Wireless Fidelity) serves to send and receive radio waves or electromagnetic waves in a free medium to be transmitted. Technological developments are expected to have a centered antenna beam orientation in a certain direction with a high gain value. High gain values ??with a centralized antenna beam can be achieved using a microstrip antenna with an array system. In this study, a rectangular 1x4 microstrip patch antenna array was designed with a rectangular slot and a T slot on the groundplane with a working frequency of 2.4 GHz made from FR4 substrate with a dielectric constant of 4.6 with a thickness of 1.6 mm, in order to get a higher gain value. compared with the single antenna from the previous study. The antenna design will be simulated using CST 2021 software. In this antenna design, 3 methods are used, namely Finite Element Method (FEM), Spectral Domain Technique (SDT), Finite Integration Technique (FIT). So that the results obtained from the antenna criteria are as follows: Return Loss -40,404 dB, VSWR 1,019, Bandwidth 4.029%, Gain 11 dBi, and the radiation pattern is directional.